Penggunaan Asbuton (Ac-Wc) Pracampur Pada Proyek Preservasi Jalan Duri – Kandis - Sp. Palas - Siak II (Pekanbaru) (E-Katalog) - Islah , Mhd.; Adeswastoto, Hanantatur (Journal of Engineering Science and Technology Management, 2023)
Asbuton is natural asphalt whose use in Indonesia is no stranger. One of the asbuton technologies that has been widely used is pre-mixed asbuton. Pre-mixed asphalt is one type of modified asphalt used in Indonesia. Pre-mixed Asphalt is processed and mixed with Pen 60/70 Asphalt at a factory that meets certain requirements, so that it is equivalent to Modified Asphalt. Premixed Asbuton products have a minimum level of purity of 90%, so they still contain a maximum of 10% fine minerals. This type of processed Pre-mixed Asphalt is the mobile container circulates directly inside the Asphalt Mixing Plant (AMP) boiler without the addition of Asphalt Pen 60/70 to produce Hot Mix Asphalt (Hotmix) which is equivalent to using Modified Asphalt. From the results of testing in the laboratory it was found that the asphalt mixture using pre-mixed asphalt has better technical properties than the conventional asphalt mixture (made using Pen 60/70 asphalt)